Hierarchical Functional Response of a Forager on a Wetland Landscape - DeAngelis, Donald L.; Yurek, Simeon; Tennenbaum, Stephen; Lee, Hyo Won (Frontiers in Ecology and Evolution, 2021)
We show that for some foragers the form that a functional response takes depends on the temporal and spatial scales considered. In representing the consumption rate of an organism, it may be necessary to use a hierarchy of functional responses. Consider, for example, the foraging of a wading bird foraging in wetland landscape characterized by a spatial distribution of potential foraging sites, such as ponds. At the smallest time scale of minutes or hours, during which a wading bird is foraging within a single site, the functional response will reflect the local density of prey, as well as features of the site that affect the feeding rate, such as water depth. At this short time scale, which is determined by the giving up time of the wading bird in a particular site, prey density may be relatively constant. The food intake from a particular pond is then the product of the time spent before giving-up time and moving to another site and the rate of prey consumption at that site. A prey-centered functional response is most appropriate for describing the prey consumption rate. We propose that over the longer time scale of a day, during which a wading bird may visit several foraging sites, the type of functional response can be considered to be patch-centered. That is, it is influenced by the spatial configuration of sites with available prey and the wading bird's strategy of choosing among different sites and decisions on how long to stay in any given sites. Over the time scale of a day prey densities may stay relatively constant, and the patch-centered functional response for a constant environment is adequate. However, on the longer time scale of a breeding season, in which changing water levels result in temporal changes in the availability of prey in sites, a third hierarchical level may be relevant. At that scale, the way in which the landscape pattern changes through time and how the wading bird responds influences the functional response. We show how this hierarchical concept applies to a colony of breeding wading birds foraging in the Everglades.